The effect of crises on firm exit and the moderating effect of firm size - Varum, Celeste Amorim (2012)
The liability of smallness assumption suggests that smaller firms face higher exit risks. However, does it apply during crises? We show that during downturns size reduces firms‟ exit risk by less; the hazard rate increases more rapidly in size.